2021
DOI: 10.1073/pnas.2021442118
|View full text |Cite
|
Sign up to set email alerts
|

A multimillion-year-old record of Greenland vegetation and glacial history preserved in sediment beneath 1.4 km of ice at Camp Century

Abstract: Understanding the history of the Greenland Ice Sheet (GrIS) is critical for determining its sensitivity to warming and contribution to sea level; however, that history is poorly known before the last interglacial. Most knowledge comes from interpretation of marine sediment, an indirect record of past ice-sheet extent and behavior. Subglacial sediment and rock, retrieved at the base of ice cores, provide terrestrial evidence for GrIS behavior during the Pleistocene. Here, we use multiple methods to determine Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 58 publications
(115 reference statements)
5
33
0
Order By: Relevance
“…These marine incursions have favored the adaptation of several marine lineages to fresh water environment (Bloom & Lovejoy, 2017;Fontenelle et al, 2021;Lovejoy et al, 2006) but also probably led to high extinctions due to the concomitant elimination of freshwater habitats in areas affected by these marine incursions (Oberdorff et al, 2019). In agreement with this last hypothesis, we found a slightly significant negative relationship between ses.MNTD and eastern sub-drainages impacted by the last see level rise during the middle Pleistocene (<1Mya, ~25m) (Christ et al, 2021), meaning that assemblages in these subdrainages are more phylogenetically clustered than expected. This may be due to high extinction rates of lowland freshwater fish species in submerged areas that reduced their overall species richness and diversification processes in the remaining, higher elevation, isolated areas (Oberdorff et al 2019).…”
Section: Regional Scale Historical Drivers Of Amazonian Phylodiversity Patternsmentioning
confidence: 90%
See 1 more Smart Citation
“…These marine incursions have favored the adaptation of several marine lineages to fresh water environment (Bloom & Lovejoy, 2017;Fontenelle et al, 2021;Lovejoy et al, 2006) but also probably led to high extinctions due to the concomitant elimination of freshwater habitats in areas affected by these marine incursions (Oberdorff et al, 2019). In agreement with this last hypothesis, we found a slightly significant negative relationship between ses.MNTD and eastern sub-drainages impacted by the last see level rise during the middle Pleistocene (<1Mya, ~25m) (Christ et al, 2021), meaning that assemblages in these subdrainages are more phylogenetically clustered than expected. This may be due to high extinction rates of lowland freshwater fish species in submerged areas that reduced their overall species richness and diversification processes in the remaining, higher elevation, isolated areas (Oberdorff et al 2019).…”
Section: Regional Scale Historical Drivers Of Amazonian Phylodiversity Patternsmentioning
confidence: 90%
“…Hoorn et al, 2010) and eastern (e.g. : Christ et al, 2021) parts and on ancient (Eocene to Miocene periods in the West; Pozo and Pebas systems) and more recent (Pleistocene marine incursions in the East) time scales. These marine incursions have favored the adaptation of several marine lineages to fresh water environment (Bloom & Lovejoy, 2017;Fontenelle et al, 2021;Lovejoy et al, 2006) but also probably led to high extinctions due to the concomitant elimination of freshwater habitats in areas affected by these marine incursions (Oberdorff et al, 2019).…”
Section: Regional Scale Historical Drivers Of Amazonian Phylodiversity Patternsmentioning
confidence: 99%
“…Johnsen et al (2001) speculated that the ice retrieved at the bottom of this core may have been deposited during the regrowth of the GrIS at the Camp Century site, having melted away during the early LIG. This suggestion has been reinforced by thermoluminescence (TL) dating of sediments at the bottom of the core (Christ et al, 2021) which indicates ice-free conditions sometime prior to 45 ka. The southern dome of the GrIS in our simulation reaches its minimum extent at 121.9 ka, before regrowing and reattaching to the northern dome at 120.5 ka.…”
Section: Comparison To Geologic Datamentioning
confidence: 95%
“…Bierman et al [2] demonstrated the utility of the paired-nuclide approach for calculating minimum total durations of exposure and burial for complex glacial histories in temperate regions-those involving multiple periods of advance and retreat. Investigations of complex glacial histories continue to be a common application of 26 Al/ 10 Be [32,33], including cases with minimal glacial erosion due to cold-based ice cover [4,34] and glacial histories inferred from marine sediment records [35,36]. 26 Al/ 10 Be has also been used to evaluate long-term erosion rates in arid regions [37], histories of tectonic uplift [38], river incision [5,6], and paleosol burial [39,40].…”
Section: Applicationsmentioning
confidence: 99%